CORPORATE SOCIAL RESPONSIBILITY (CSR) FOR THE REMEDY OF AFFECTED PEOPLE IN CRIMES AGAINST HUMANITY CASE IN NORTH ACEH, INDONESIA - Ainal Zahra Nabila; Lena Farsia (Student Journal of International Law, 2022)
This paper examines  ExxonMobil's Corporate Social Responsibility (CSR) programs for the remedy of affected people in the crimes against humanity cases that occurred in North Aceh, Indonesia. The method applied to this paper is normative research that describes the case, gathers, and organizes a wide variety of data from the document to produce a report about the role of CSR programs for the remedy of the affected people in crimes against humanity cases committed by the party that is affiliated with the ExxonMobil, (Indonesian National Armed Forces). This paper found that the role of CSR for the remedy of affected people in ExxonMobil crimes against humanity case can be handled by corporate citizenship, which is a limited concept of CSR that comply with international guidance and standard of CSR.